The inhibitory effects of ginsenosides on periodontitis pathogenic bacteria - Qiuyang Lei; Jianrong Chen; Ye Yuan; Chenxing Hu; Zhiying Lin; Shuang Yang; Kevin H. Mayo; Yifa Zhou; Lin Sun; Wenzhi Song (Frontiers in Microbiology)
Periodontitis is mainly caused by bacterial destruction of periodontal tissue in dental plaque. Commonly used antibiotic treatment has some shortcomings, such as incomplete sterilization, drug resistance, and local flora imbalance. Because of this, there is a need to identify safe and non-drug resistant health products with high antibacterial activity. Ginsenosides, the primary active component in ginseng, have been shown to be antibacterial. In this study, we investigated the inhibitory effects of ginsenosides on Porphyromonas gingivalis and Fusobacterium nucleatum, along with their structure–activity relationships and mechanisms of action. Our results show that total ginsenosides elicit a significant inhibitory effect on the growth of periodontal pathogens, with antibacterial effects from PPD-type saponins being greater than those from PPT-type saponins. Among different monomer saponins, Rd had the best antibacterial effect and inhibited the growth of periodontal pathogens at 250 μM. Mechanistic analyses indicated that total ginsenosides mainly function at inhibiting biofilm formation by reducing cell surface hydrophobicity and extracellular polysaccharide content. Our study provides the basis for development of new, plant-based treatment drugs against periodontal disease.